Enhanced dendrite resistance in reversible electrochemical pneumatic batteries with nanoimprinted nanowire anodes for jamming robots - Ge, Junyu (2024)
Traditional electric robots often rely on heavy gear units or expensive force–torque sensors, whereas pneumatic robots offer a cost-effective and simple alternative. However, their dependence on noisy and bulky pneumatic systems, such as compressed air technology, limits their portability and adaptability. To overcome these challenges, we have developed a reversible electrochemical pneumatic battery (REPB) that is compact, noise-free, energy-efficient, and portable. This innovative REPB, principled by the electrochemical redox reactions of zinc–air batteries, can simultaneously supply both electric and pneumatic power, either positive or negative pressure. Its modular, multi-stack structure allows for the easy customization of power output and capacity to suit various applications. We demonstrate the utility of REPB through its application in jamming robots, such as a novel soft yet robust gripper that merges the strengths of hard and soft grippers, enabling universal robotic gripping. This work presents a groundbreaking approach to powering devices that require pneumatic support.